Structure and evolution of interstellar carbonaceous dust. Insights from the laboratory - Herrero, Víctor J.; Jiménez-Redondo, Miguel; Peláez, Ramón J.; Maté, Belén; Tanarro, Isabel (Frontiers in Astronomy and Space Sciences, 2022)
A large fraction of interstellar carbon is locked up in solid grains. The nature, origin and evolution of these grains have been investigated for decades. A combination of observations, models and experiments indicate that carbonaceous dust is mostly made of a mixture of grains composed almost exclusively of carbon and hydrogen. They have different proportions of aliphatic and aromatic structures, and a variable H/C ratio. Their sizes can vary typically between the nm and the hundreds of nm. Carbonaceous grains are largely formed in the envelopes of carbon rich asymptotic giant branch (AGB) stars and evolve in the interstellar medium, where they can be transformed or destroyed by the effects of hydrogen atoms, UV radiation, cosmic rays or shock waves from supernovae. Surviving grains eventually enter dense clouds and participate in the cloud collapse leading to star formation, closing thus their lifecycle. Within this general picture, there are doubts and issues that cannot be solved just by observation and modeling and require laboratory work. In this article we provide an overview of the development and present state of the field indicating open problems and debated questions. We stress recent experimental progress in the understanding of dust formation, both in circumstellar envelopes and the cold interstellar medium, and also in the energetic processing of dust analogs, that points to a possible top down chemistry in the diffuse medium, and especially in photon irradiated regions.